A 3D‐Bioprinted Functional Module Based on Decellularized Extracellular Matrix Bioink for Periodontal Regeneration. Issue 5 (14th December 2022) - Yang, Xueting; Ma, Yue; Wang, Xiuting; Yuan, Shengmeng; Huo, Fangjun; Yi, Genzheng; Zhang, Jingyi; Yang, Bo; Tian, Weidong
Abstract: Poor fiber orientation and mismatched bone–ligament interface fusion have plagued the regeneration of periodontal defects by cell‐based scaffolds. A 3D bioprinted biomimetic periodontal module is designed with high architectural integrity using a methacrylate gelatin/decellularized extracellular matrix (GelMA/dECM) cell‐laden bioink. The module presents favorable mechanical properties and orientation guidance by high‐precision topographical cues and provides a biochemical environment conducive to regulating encapsulated cell behavior. The dECM features robust immunomodulatory activity, reducing the release of proinflammatory factors by M1 macrophages and decreasing local inflammation in Sprague Dawley rats. In a clinically relevant critical‐size periodontal defect model, the bioprinted module significantly enhances the regeneration of hybrid periodontal tissues in beagles, especially the anchoring structures of the bone–ligament interface, well‐aligned periodontal fibers, and highly mineralized alveolar bone. This demonstrates the effectiveness and feasibility of 3D bioprinting combined with a dental follicle‐specific dECM bioink for periodontium regeneration, providing new avenues for future clinical practice. Abstract : A biomimetic and functional periodontal module is developed using the methacrylate gelatin/decellularized extracellular matrix bioink by employing a 3D bioprinting approach. The module simulates natural anatomical complexity and biochemical microenvironment, and exhibits strong biological induction activity. Well‐aligned periodontal fibers, highly mineralized alveolar bone, as well as satisfactory bone–ligament interface integration are achieved after 3 months of implantation in vivo.